Body Mass Index in Religious Contexts: Exploring the Multilevel Influences of Religion - Nie, Fanhao (Journal of religion and health, 2021)
Can the religious values of an entire geographic area affect the BMI of people living in that same area, even people with different religious values? Although prior research has demonstrated that individual religious characteristics are associated with individual BMI, less is known about how the overall religious context influences BMI. Using multilevel analyses on two waves of the National Study of Youth and Religion merged with county-level variables, this study finds that a county’s higher Catholic population share is associated with lower individual BMI even after controlling for various individual and county-level variables. Surprisingly, this Catholic contextual effect on BMI applies to almost everyone living in a predominantly Catholic county regardless of individual Catholic identity and residential movement across counties. In contrast, county-level conservative Protestant population share is linked with higher BMI. However, this conservative Protestant contextual effect is explained by county-level socioeconomic variables.